2020
DOI: 10.1088/1361-6420/ab4aec
|View full text |Cite
|
Sign up to set email alerts
|

Fast acoustic source imaging using multi-frequency sparse data

Abstract: We consider the acoustic source imaging problems using multiple frequency data.Using the data of one observation direction/point, we prove that some information (size and location) of the source support can be recovered. A non-iterative method is then proposed to image the source for the Helmholtz equation using multiple frequency far field data of one or several observation directions. The method is simple to implement and extremely fast since it only computes an indicator function on the interested domain us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 21 publications
0
44
1
1
Order By: Relevance
“…The following theorem gives a uniqueness result on determine the strip by using only compressional far field data or shear far field data at a fixed observation direction. The proof follows the related results for inverse acoustic source scattering problems [1]. Theorem 3.5.…”
Section: Scattering Of Sourcesmentioning
confidence: 60%
See 1 more Smart Citation
“…The following theorem gives a uniqueness result on determine the strip by using only compressional far field data or shear far field data at a fixed observation direction. The proof follows the related results for inverse acoustic source scattering problems [1]. Theorem 3.5.…”
Section: Scattering Of Sourcesmentioning
confidence: 60%
“…Phaseless inverse source problems. The forward problems are computed the same as in [1]. In all examples, forx ∈ Θ, we consider multiple frequency far field data u ∞ F,s (x, k j ), j = 1, · · · , N, where N = 20, k min = 0.5, k max = 20 such that k j = (j − 0.5)∆k, ∆k = kmax N .…”
Section: 2mentioning
confidence: 99%
“…In the last decades, great efforts had been devoted to the numerical methods for the inverse source problem of determining an acoustic source. We refer interested readers to [3,7,9,22,23,25,27] for the sampling method, the continuation method, the eigenfunction expansion method and the Fourier method for recovering the static sources and [20,21] for the investigations on imaging the moving point sources.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in [26], it is shown that the maximum and minimum distance between measurement point and the support of the source can be uniquely determined by using the electric field at a single point. The idea is from [1,23,39] for inverse acoustic source problem with multi-frequency sparse far field data.…”
mentioning
confidence: 99%
“…We first give a uniqueness result following the ideas for the inverse acoustic and elastic scattering problems [1,28].…”
mentioning
confidence: 99%